ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KEPATUHAN WAJIB PAJAK ORANG PRIBADI (Studi Pada Kantor Pelayanan Pajak Pratama Semarang) - Bona Imelda; Haryanto Haryanto (Diponegoro Journal of Accounting, 2014)
This study aims to analyze factors that influence tax compliance in KPP Pratama Semarang. The variables which are used in this research is taxpayer’s compliance as dependent variable, and knowledge and understanding of tax regulations, perception of the tax system’s effectiveness, tax authorities’ service, and tax conflict as the independent variables. This research also using 3 (three) control variables, such as tax penalties, construction of public facilities, and the level of education. This study uses quantitative research methods, where the data obtained from questionnaires with  Convenience Sampling method. Data analysis in this research uses multiple linear regression analysis with SPSS 20.00 for Windows.The results of this research are as follows: (1) knowledge and understanding of tax regulations on taxpayer’s compliance is positive and significant, (2) perception of the tax system’s effectiveness did not significantly gives positive influence to taxpayer’s compliance, (3) tax authorities’ service on taxpayer’s compliance is positive and significant, (4) tax conflict did not significantly gives negative influence to taxpayer’s compliance, (5) tax penalties did not significantly gives positive influence to taxpayer’s compliance, (6) construction of public facilities on taxpayer’s compliance is positive and significant, (7) level of education on taxpayer’s compliance is positive and significant